INTEGRITY ZONE DEVELOPMENT STRATEGIC POLICY AS LEGAL MEASURES FOR CORRUPTION PREVENTION AT UIN SALATIGA - Ali Mahrus; Desiderius priyo sudibyo; Asal wahyuni erlin mulyadi (Faculty of Law, Universitas Pekalongan, 2023)
The aims of this study are 1) to find out what factors have caused the failure and success of the construction of the Integrity Zone at IAIN Salatiga in achieving the title of a Corruption-free Region; 2) To find out the Integrity Zone development policy in an effort to prevent corruption at IAIN Salatiga. This research uses a descriptive qualitative method. The stages that the researcher will go through include: the data reduction stage, data presentation, and conclusion drawing (verification). The results of the research are: 1) The most significant cause of failure is due to budget refocusing caused by the handling of the Covid-19 pandemic, which results in sudden budget revisions or the emergence of rules that require changing the program of activities that have been set at the beginning; 2) There are 6 aspects of success in the development of the Integrity zone at IAIN Salatiga including change management, management arrangements, management system arrangements, strengthening supervision, strengthening the quality of public services and making one-stop integrated services; 3) With the establishment of an integrity zone policy at IAIN Salatiga, it can make agents of change in work units, because ZI is not only a matter of orderly administration but also how to work units can serve the community.